2019
DOI: 10.4314/gjgs.v17i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and bacteriological parameters of surface water quality in part of Oban Massif, Nigeria

Abstract: The present study presents preliminary investigation on the physico-chemical and bacteriological parameters of surface water samples collected, during the wet and dry seasons, from streams in Orem and environs, a typical Basement terrain in southeastern Nigeria. The intension was to evaluate the suitability of the water for domestic and agricultural uses. Results generally indicate normal water temperature, especially for the tropic; pH reflecting slightly acidic conditions; low EC and water hardness which res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
1
8
1
Order By: Relevance
“…Least value for Mg 2+ 1.24 ± 0.55 mg/L occurred in the river during the wet season (Table 2). Higher levels of Cland NO 3 in the dry season than in wet season is probably due to dilution effect, and demonstrate an increase in the discharge of the respective components into the water body with time (Ugbaja and Ephraim, 2019).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Least value for Mg 2+ 1.24 ± 0.55 mg/L occurred in the river during the wet season (Table 2). Higher levels of Cland NO 3 in the dry season than in wet season is probably due to dilution effect, and demonstrate an increase in the discharge of the respective components into the water body with time (Ugbaja and Ephraim, 2019).…”
Section: Resultsmentioning
confidence: 94%
“…According to Ugbaja and Ephraim (2019) the acidic nature of the water samples is a possible reflection of the presence of high levels of free CO 2 in the waters. An important problem associated with acidic nature of surface water is that these water favour the mobility of non-biodegradable and hazardous trace elements within them (Ephraim and Ajayi, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low conductivity values could be due to poor and rather insoluble geologic rock and mineral types [65]. Total suspended solids TSS of the water samples from all communities in the three Local Areas were all above NSDWQ standard of 0.01 mg/L [66] and showed TSS range/average of 0.34 -0.68 mg/L (0.50 mg/L), 0.36 -0.68 mg/L (0.52 mg/L) and 0.14 -2.04 mg/L (0.72 mg/L) for Awka South, Anaocha and Awka North respectively. The result of the elemental analyses (Tables 4-6) showed that the concentrations of lead and arsenic in water samples from communities in Awka South were all above the WHO standard of 0.01 mg/L [62] [63], except samples from St Joseph Umuawulu, GMG Nibo, Ngodo Nise and St John Nise where lead and arsenic were absent.…”
Section: Resultsmentioning
confidence: 88%
“…Human being uses this supply as wellspring of irrigation, domestic water [2]. The increased rate of urbanization and industrialization has been threatened the quality of water available for living organisms [3]. Water Quality Index is a tool which tells the standard and level of drinking water [1].…”
Section: Physico-chemical and Heavy Metals Analysis Of Drinking Watermentioning
confidence: 99%